Clinical Insights into Klebsiella pneumoniae: Prevalence, Antibiotic Resistance, and Virulence Gene Analysis in Hospitalized Patients - Aziz, Omed Khan; Amenn, Sirwan Muhammed (Sulaimani Journal for Pure and Applied Sciences, 2025)
Background: Klebsiella pneumoniae has two pathotypes: hypervirulent (hvkp) and classical (ckp). Hypervirulent kp produces more severe systemic infections. The study aimed to isolated and identified K. pneumoniae from clinical specimens, studied the frequency of hvkp compared to ckp, evaluating effectiveness of antibiotics against them, and examined virulence gene distribution. Methods: Samples from admitted patients were cultivated on MacConkey agar, and pink colonies were identified as Klebsiella pneumonia using conventional biochemical methods. K pneumoniae was also confirmed, and Vitek 2 sensitivity was assessed. String tests were used for hypermucoviscosity. Molecular identification of the 16s-23s ITS gene and virulence-associated genes entB, rmpA, magA evaluated by multiplex PCR. Results: The identification of 54 isolates initially biochemically identified as K. pneumoniae was verified by PCR amplification of the 16S–23S ITS region. 11 (20.4%) showed hvkp and 43 (79.6%) showed cKp. All and cKp isolates had the entB gene, however only one had the rmpA gene (9%). Moreover, None of the isolates had magA genes. Results of antibiotic susceptibility test exhibited, with complete resistance noted for ampicillin and substantial resistance for cefazolin, ceftriaxone, ceftazidime, and several other antibiotics. In contrast, hvKp isolates had reduced resistance rates for ceftriaxone piperacillin/tazobactam, cefepime, gentamicin, ceftazidime and trimethoprim/sulfamethoxazole. Tigecycline and colistin were the only antibiotics that worked against cKp, with 4.6% of isolates resistant. Conclusion, the study confirmed K. pneumoniae isolates, only a small number were classified as hvKp, all containing the entB gene, while cKp isolates showed significant antimicrobial resistance, effectively treatable only with tigecycline and colistin
Keywords: Klebsiella pneumoniae; Virulence factors; Antibiotic resistance; hypervirulent (hvkp); classical (ckp)